Integração Interfuncional 4.0 em processos de desenvolvimento de produtos - Oliveira, Juliana Amaral (2019)
The transformations towards the digitalization of processes that take place in Industry will contribute to the movement of organizations to innovate and rethink ways of working in collaboration and partnerships, from meeting customer demands to creating ever smarter products and services, means by which companies increase their competitive strength. In this sense, the objective of this paper is to characterize the initiatives of cross-functional integration in product development processes and how these elements can be studied in companies using Industry 4.0 technologies. Thus, a systematic review was performed to characterize the literature on functional integration initiatives in product development processes in the context of Industry 4.0 technologies in two of the main international databases (Scopus and Web of Science), and initial analysis of the the documents were performed by using the VOSViewer software for construction and visualization of bibliometric networks. Subsequently, a content analysis of the selected articles was made after criteria that mentioned factors of cross-functional integration in product development processes in the smart factories environment. Only 16 articles cite cross-functional integration and most journals are technical and non-managerial in nature, highlighting the need to develop research from a more managerial perspective of Industry 4.0. The reason is that there is currently more focus on technology development than on generating cooperation between the different components of the product development process.